Knowledge sharing practices in informal scholarly communication amongst academics in Poland - Świgoń, Marzena (Malaysian Journal of Library and Information Science, 2017)
This study explored knowledge sharing practices in Polish informal scholarly communication. The informal channels of communication include discussion, conversation, information exchange in both forms: face to face and via information and communication technologies. The study was carried out among the Polish academic community using a structured online questionnaire, which contained 88 questions (closed and partly open). Respondents consisted of academics: PhD, PhD with Habilitation, and Professors, employed in several types of universities and academia located throughout the country. A total of 1558 academics responded to the survey, representing all academic disciplines –humanities, social sciences, technical and life sciences. The Polish academic community created rather homogenous networks, generally limited to their own disciplines. The favourite platform to share knowledge was unofficial talks during conferences and seminars. The preferable form of knowledge sharing practices was face to face talks, despite the development of modern information and communication technologies. The biggest barrier to knowledge sharing was the lack of time for free conversations. The most important motivator could be the interest of colleagues. Polish researchers commonly used only electronic mail and rarely used social media and blogs to share knowledge. This is the first national survey about knowledge sharing practices in Polish academic environment.